Fundus changes in mesangiocapillary glomerulonephritis type II: clinical and fluorescein angiographic findings. Issue 11 (November 1989) - Duvall-Young, J; Short, C D; Raines, M F; Gokal, R; Lawler, W
Abstract : Previously we have demonstrated a deposit in Bruch's membrane in a single case of mesangiocapillary glomerulonephritis type II. We studied a group of patients with this disease and described extensive clinical and fluorescein angiographic abnormalities, which were in marked contrast to the findings in a group of patients with other forms of glomerulonephritis. This finding contributes to our understanding of the pathophysiology of the complex of the retinal pigment epithelium, Bruch's membrane, and choriocapillaris.